The Hukou System as China’s Main Regulatory Framework for Temporary Rural-Urban Migration and its Recent Changes - Zhang, Jijiao (DIE ERDE – Journal of the Geographical Society of Berlin, 2012)
More than 50 years ago China’s government established the hukou system in order to prevent rural urban migration, requiring people to stay in the area where they were registered. Migrating to the city without being registered as ‘urban’ implied that the migrants had no access to education, food, housing, employment and a variety of other social services. In 1982, when unskilled labour was in short supply in the booming cities, a programme of gradual reform was started which eased the strict regulations. However, the level of liberalisation varied from one province to another and from one metropolis to the other, creating remarkable differences in the regulatory framework. The paper describes the history of the hukou system and its consequences as well as its reforms from the early beginnings to the present day and discusses the need for further reform.